The Mediating Effect of Job Satisfaction on the Relationship of Employee Engagement and Employee Performance: Empirical Evidence from non-managerial employees of State Bank of India Raipur, Chhattisgarh region - Singh, Dr. Roopendra; Kumar, Dr. Hemant; Kalla, Dr. Nitin; Pujari, Dr. Bharati (The journal of contemporary issues in business and government, 2022)
An organization's progress depends on employee engagement and performance. The satisfaction level also leads to their performance as well as the organization's overall growth. Customers perceived State Bank of India as a reliable bank especially in rural India and the employees doing the job in that bank are regarded as the caretaker and custodians of the villager’s hard- earned money. The study analyzes the effect of employee engagement of non-managerial employees at SBI in the Raipur region of Chhattisgarh on their employee performance when mediated through their job satisfaction. The predictor variable was employee engagement, the mediator variable was job satisfaction and the dependent variable was employee performance. The findings revealed that there was a significant indirect effect of Employee Engagement on Employee Performance through Job Satisfaction.